Anisotropic Dirac Fermions in BaMnBi2 and BaZnBi2 - Ryu, Hyejin; Park, Se Young; Li, Lijun; Ren, Weijun; Neaton, Jeffrey B.; Petrovic, Cedomir; Hwang, Choongyu; Mo, Sung-Kwan (Nature Publishing Group, 2018)
We investigate the electronic structure of BaMnBi2 and BaZnBi2 using angle-resolved photoemission spectroscopy and first-principles calculations. Although they share similar structural properties, we show that their electronic structure exhibit dramatic differences. A strong anisotropic Dirac dispersion is revealed in BaMnBi2 with a decreased asymmetry factor compared with other members of AMnBi(2) (A = alkali earth or rare earth elements) family. In addition to the Dirac cones, multiple bands crossing the Fermi energy give rise to a complex Fermi surface topology for BaZnBi2. We further show that the strength of hybridization between Bi-p and Mn-dZn-s states is the main driver of the differences in electronic structure for these two related compounds.